Pandangan Pramoedya Terhadap Resistansi Perempuan dalam Novel Era Revolusi dan Reformasi - Ridwan, Iwan; Widiasturi, Aries; Yulianeta, Yulianeta (Adabiyyāt: Jurnal Bahasa dan Sastra, 2016)
A literary work reflects world vision of its writer, including the world of women. Pramoedya Ananta Toer participated to reveal the idealism of women’s resistance in revolution and reformation era through the characters of his story. Obtaining the world view of the writer toward women is important. This research aims to examine women’s resistance in the Revolution and Reformation era within 3 novels by Pramoedya Ananta Toer. This research uses qualitative method with content and sociological analysis model. The problems of the analysis are (1) the historic flaming in which Pramoedya Ananta Toer writes Larasati, MSBE, and PRdCM; and (2) world’s view of Pramoedya Ananta Toer toward women’s resistance in Larasati, MSBE, and PRdCM. To explain the world’s view of the writer, this research also applies Lucien Goldmann’s genetic structuralism. The objective of this research is to reveal the women’s resistance within three prominent characters who have fought in some different ways for justice in revolution and reformation era. This confirms that Pramoedya brings justice and gender equality in the world of women.